The effects of co-prescription of pantoprazole on the clozapine metabolism - Kuzin, Maxim; Schoretsanitēs, Geōrgios; Haen, Ekkehard; Dammann, Gerhard; Hiemke, Christoph; Gründer, Gerhard; Paulzen, Michael (Pharmacopsychiatry, 2020)
BACKGROUND: Polypharmacy including somatic medications such as proton pump inhibitors is a common phenomenon in psychiatric care. The aim of this study was to evaluate the pantoprazole effects on clozapine metabolism. METHODS: A large therapeutic drug-monitoring database containing plasma concentrations of CLZ was analyzed. The results were stratified into four groups: a non-smoking (n=250) and a smoking group (n=326), and two groups co-medicated with pantoprazole: non-smokers (n=26) and smokers (n=29). The analysis was based on the non-parametrical Mann-Whitney U test (M-W-U) with a significance level of 0.05. RESULTS: Differences reached statistical significance for pharmacokinetic parameters between CLZ monotherapy and co-medication with pantoprazole neither in smokers nor in non-smokers (p>0.05 for M-W-U in pairwise comparisons). In patients with clozapine monotherapy, smokers had a higher daily dosage of CLZ compared to non-smokers (mean dosage 363±181 vs. 291±145 mg/day, p<0.001 for M-W-U). CONCLUSIONS: Adding pantoprazole to an ongoing treatment with clozapine does not alter the metabolism of clozapine to a significant extent.
Gesehen am 25.01.2021